Performance valuation of onion (Allium cepa L.) genotypes under different levels of salinity for the development of cultivars suitable for saline regions - Alam, Md. Ashraful; Rahman, Md. Atikur; Rahman, Md. Marufur; Hasan, Md. Mahmudul; Naher, Shamsun; Fahim, Abu Hena Faisal; Mottalib, Md. Abdul; Roy, Srabanti; Islam, Md. Rafiqul; Mozumder, Shailendra Nath; Alsuhaibani, Amnah Mohammed; Gaber, Ahmed; et al. (Frontiers in Plant Science, 2023)
Abiotic stress especially salt stress is one of the major barriers to crop production all over the world. Crops like onion enlisted in the glycophytic group are more sensitive to salinity stress. A huge study has already been done and still going on regarding the influence on the growth and development of crops under salinity stress. One of the major targets of the research is to develop genotypes having enhanced performance under stress environments. The world needs more of these types of genotypes to combat the ever-growing salt-stressed soils. Therefore, a number of germplasm were studied during the 2019-20 and 2020-21 seasons under different salt concentrations to identify tolerant genotypes as well as to study the plants' responses at different growth stages against elevated salinity lev-els. A two years study was executed where, germination potential was evaluated in the 1st year and carried out in petri-dish-culture of seeds, while, plastic pot culture was followed for plant establishment and bulb development evaluation during the 2nd year. Four different saline water solutions having different salt concentrations (0, 8, 10 and 12 dSm-1) were applied to the petri-dishes and pots as the source of water for plants in both seasons. Results indicated that a significant reduction in plants performance occurs under higher salinity levels. Salt concentration had an adverse impact on germination, leaf development and growth, the height of plants, bulb size and shape along with the bulb weight of onion. All the growth phases of onion are sensitive to elevated concentrations. Variable performances were observed in the genotypes under stress conditions and a few genotypes (Ac Bog 409, Ac Bog 414, Ac Bog 424, Ac Bog 430, Ac Bog 417, Ac Bog 419, Ac Bog 420, Ac Bog 422 and Ac Bog 425) were identified having some sort of tolerance to salt stress which might be recommended for mass production. Tolerance indices could successfully be applied in selecting the salt-tolerant genotypes. Thus, the present findings and the identified genotypes could be further utilized in salt stress improvement research on onion.